2017
DOI: 10.1007/s00167-017-4607-6
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cruciate ligament tibial insertion site is elliptical or triangular shaped in healthy young adults: high-resolution 3-T MRI analysis

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 41 publications
2
36
0
Order By: Relevance
“…The sensitivity analysis of ACL relative elongation was performed by changing the ratio of the point that divided into AMB and PLB (Supplementary Material). The validity of this technique for identifying AMB and PLB tibial insertions was confirmed using a previously reported data set . The AMB and PLB centroids were positioned at the centroid of the AMB and PLB respective areas (Fig.…”
Section: Methodssupporting
confidence: 53%
See 2 more Smart Citations
“…The sensitivity analysis of ACL relative elongation was performed by changing the ratio of the point that divided into AMB and PLB (Supplementary Material). The validity of this technique for identifying AMB and PLB tibial insertions was confirmed using a previously reported data set . The AMB and PLB centroids were positioned at the centroid of the AMB and PLB respective areas (Fig.…”
Section: Methodssupporting
confidence: 53%
“…Moreover, the sample size in the current study is similar in size to most previous studies that investigated in vivo ACL strain or elongation . Second, due to the inability to differentiate AMB and PLB insertions on MRI, the insertion sites were calculated according previous reports on the anatomy of the ACL insertions and validated using a previously reported data set . A third limitation is that the ACL length was normalized by the length at static knee full extension during MRI; thus only relative ACL elongations could be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between our results and those of other authors, by the various modes of evaluation, is found in ►Table 3. [3][4][5][6][7][8][9][10][11][12][13][18][19][20][21][22][23][24] In fact, Lord et al 25 published a study of the function of the ACL tibial insertion fibers in the resistance of anterior and rotational displacements, with robotics, in six degrees of freedom of movement. They concluded that the central, posterior and lateral fibers of the ACL tibial insertion play a secondary role in the restriction of tibial displacements and that the most important fibers are the anterior and the anteromedial peripheral portion.…”
Section: Discussionmentioning
confidence: 99%
“…4 Therefore, anticipating the dimensions of the ACL insertion can be valuable for better surgical planning. This can be done by CT scan 5,6 or magnetic resonance imaging (MRI), [7][8][9][10][11] but it can also be predicted by the individual physical characteristics. 3,4 In this decade, some authors sought to correlate the weight and height of patients with the size of their tibial ACL insertion.…”
Section: Introductionmentioning
confidence: 99%